Sustainable Growth Rate Model in Indonesia Manufacturing Firms - Vina Christina Nugroho (The Winners, 2020)
Regarding the importance of Sustainable Growth Rate (SGR) calculation for firms as a basic of financial decision, many previous studies had highlighted the variability of SGR calculation. The research’s first objective focused on two methods of SGR calculation and figured out the determinant factors (internal and external) that affect firm’s SGR. One method focused on different determinants of SGR when industry or firm specific aspects were considered. Whereas, SGR (II) focused on determinant of SGR when firms are reluctant to issue new equity. The second objective was to investigate the determinant factors towards SGR in both models. Sample for the research was public-listed manufacturing firms in Indonesia from 2011 to 2019. The result shows that there is significant difference between the two methods, and not to mention that Return on Equity (ROE) becomes the only factor that affect SGR (in both models). The implication is due to the limited amount of time, so the research can only compare two different method of SGR.